Effect of cations (Mg2+, Zn2+, Cd2+) on formation of the mineral phase in Ca(NO3) 2 -Mg(NO3) 2-Na2HPO4-H2O system - Golovanova, O.A.; Shlyapov, R.M.; Amerkhanova, Sh.K.; Uali, A.S.; Vlasov, V.A. (IOP PUBLISHING LTD, 2015)
Synthesis of hydroxyapatite in the system Ca(NO3)2-Me(NO3)2-NaHPO4-H2O with pH in the range of 6-12.2 is performed, and hydroxyapatite of B-type is formed. The effect of magnesium, zinc and cadmium ions on the properties of hydroxyapatite is studied. It is shown that as the concentration of these ions increases, the crystallinity of hydroxyapatite and the Ca/P ratio decreases. It is found that in all the experiments Zn2+ cations affect the hydroxyapatite structure to a lesser extent which results in less structural defects, wherein the Ca/P ratio attains the highest values. It is shown that the solubility of the samples containing zinc ions is greater than that of the samples with other additives.
Keywords: Hydroxyapatite structure; Dissolution; Crystallization; Acidity; Cationic substitution